Composite current collector, manufacturing method and device thereof and battery using composite current collector
By depositing a composite liquid collector of aluminum and alumina layers in a vacuum environment, the problem of the existing self-breaking current collector is easily broken during transportation, and the effect of automatically breaking the circuit in a large-capacity battery cell is achieved to eliminate the risk of fire and explosion.
Patent Information
- Application Number
- CN202411793825.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-04
AI Technical Summary
The existing self-breaking current collector is susceptible to vibration during transportation and the pre-etching process is complex and is not suitable for large-scale manufacturing, making it difficult to control the risk of fire and explosion in large-capacity battery cells.
The aluminum is heated to a preset temperature in a vacuum environment, and it is evaporated and deposited on the surface of the polymer film to form a first aluminum layer, and then an alumina layer is deposited on the surface of the first aluminum layer to form an interlaced aluminum and aluminum trioxide layer to reduce the ductility so as to crack itself during mechanical deformation.
By automatically breaking the circuit when the battery cell structure is damaged, the risk of battery cell fire and explosion is eliminated, and the production cost is low, it is suitable for large-scale manufacturing.
Smart Images

Figure CN119560569A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite current collectors, and in particular to a composite current collector and a manufacturing method and device thereof, and a battery using the composite current collector. Background Art
[0002] With the development of energy storage cells, cells are getting bigger and bigger, and the energy density is growing. High energy density requires pushing the oxidation positive electrode and the reduction negative electrode in a limited space, which greatly increases the risk of fire and explosion of large-capacity cells. Instantaneous internal short circuits caused by mechanical deformation are the main cause of violent fires and explosions in batteries. Therefore, it is very important to establish a high resistance to mechanical deformation for the development of lithium-ion batteries. In terms of electrode design, researchers have proposed self-fracture electrodes. When subjected to mechanical shock, the electrode collapses, thereby limiting the short-circuit current by isolating the damaged part from the rest. Self-fractured current collectors are made by pre-etching concentric cracks. However, during transportation, pre-etched cracks are easily broken by vibration, making them difficult to apply in actual large-scale applications. In addition, there are some problems with the pre-etching process, which is too complicated to be used in large-scale manufacturing. Summary of the invention
[0003] In order to overcome the defects in the prior art, the present invention provides a composite current collector and a method and device for making the same, and a battery using the composite current collector. The composite current collector manufacturing method only requires heating aluminum to a preset temperature in a vacuum environment, evaporating aluminum and depositing it on the surface of a polymer film to form a first aluminum layer, providing oxygen to react with the aluminum, depositing an aluminum oxide layer on the surface of the first aluminum layer, and depositing the first aluminum layer and the aluminum oxide layer on both sides of the polymer film to obtain a composite current collector. The method has low manufacturing cost, and the manufactured composite current collector can automatically break the circuit by cutting off the electronic channel at the moment when the battery cell structure is damaged and short-circuited, eliminating the risk of fire and explosion of the battery cell.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a composite current collector, comprising:
[0005] A first roller and a second roller are arranged in a vacuum chamber, wherein the first roller unwinds the polymer film and the second roller rewinds the polymer film;
[0006] Using an aluminum vapor evaporation device, vapor aluminum is evaporated and deposited onto the surface of the unfolded portion of the polymer film. During the deposition process, the polymer film moves from the first roller toward the second roller at a speed of 0.8 m / s to 1.2 m / s, thereby depositing a first aluminum layer with a thickness of 0.8 μm to 1.2 μm on the surface of the polymer film;
[0007] Injecting oxygen into the vacuum chamber, under the action of the aluminum vapor evaporation device, the vapor aluminum and oxygen react to generate aluminum oxide and deposit it on the surface of the first aluminum layer. During the deposition process, the polymer film having the first aluminum layer moves from the second roller toward the first roller at a speed of 3m / s to 5m / s, thereby depositing an aluminum oxide layer with a thickness of 0.9nm to 1.1nm on the surface of the first aluminum layer;
[0008] The first aluminum layer and the aluminum oxide layer are deposited on both side surfaces of the polymer film to obtain a composite current collector.
[0009] Through the above scheme, aluminum is evaporated in a vacuum environment and deposited on the surface of the polymer film to form a first aluminum layer, and oxygen is provided to react with aluminum to deposit an aluminum oxide layer on the surface of the first aluminum layer. The first aluminum layer and the aluminum oxide layer are deposited on both sides of the polymer film to obtain a composite current collector. This method has low production cost.
[0010] Traditional aluminum current collectors and single-layer current collectors have stubborn ductility under mechanical deformation, maintaining a complete electron movement path. Ultimately, due to the large amount of Joule heat generated, the internal short circuit caused thermal runaway of the battery. The current collector disclosed in this scheme is composed of staggered aluminum and chlorine trioxide layers, and the nano-scale aluminum trioxide reduces the ductility of the pure aluminum layer. It is easier to crack by itself under the nail deformation load, so it can automatically break the circuit by cutting off the electronic channel at the moment when the battery cell structure is damaged and short-circuited, eliminating the risk of fire and explosion of the battery cell.
[0011] Furthermore, during the deposition process, the aluminum vapor evaporation device heats the aluminum to 1400° C. Under the condition of 1400° C., the aluminum reaches a relatively high evaporation rate, ensuring that a first aluminum layer with a thickness of 1 μm can be deposited in one evaporation.
[0012] Furthermore, during the deposition of the first aluminum layer, the polymer film moves from the first roller toward the second roller at a speed of 1 m / s, and a first aluminum layer with a thickness of 1 μm is deposited on the surface of the polymer film. The polymer film is controlled to move at a speed of 1 m / s, combined with the high evaporation rate of aluminum, to further ensure that a first aluminum layer with a thickness of 1 μm can be deposited in one evaporation.
[0013] Furthermore, during the deposition of the aluminum oxide layer, the polymer film moves from the second roller toward the first roller at a speed of 4 m / s, and a 1 nm thick aluminum oxide layer is deposited on the surface of the first aluminum layer. According to experiments, in an environment of 1400°C and with the polymer film moving at a speed of 4 m / s, a 1 nm thick aluminum oxide layer can be deposited on the surface of the first aluminum layer.
[0014] Furthermore, during the deposition of the aluminum oxide layer, the polymer film moves from the second roller toward the first roller at a speed of 6 m / s, and deposits an aluminum oxide layer with a thickness of 0.5 nm on the surface of the first aluminum layer. According to experiments, in an environment of 1400°C, with the polymer film moving at a speed of 6 m / s, an aluminum oxide layer with a thickness of 0.5 nm can be deposited on the surface of the first aluminum layer.
[0015] Furthermore, the polymer film includes any one of PET, PP, and PI, and the polymer film has a thickness of 5 μm to 7 μm. In the present application, the polymer film is a polyethylene terephthalate film.
[0016] A composite current collector prepared according to the above method comprises:
[0017] A polymer film layer, wherein the polymer film layer is made of polyethylene terephthalate;
[0018] A first aluminum layer, wherein the first aluminum layer is disposed on both side surfaces of the polymer film layer;
[0019] an aluminum oxide layer, the aluminum oxide layer being disposed on a side of the first aluminum layer away from the polymer film layer
[0020] A device for making a composite current collector according to the above method comprises:
[0021] Vacuum chamber;
[0022] An aluminum vapor evaporation device, which is disposed in the vacuum chamber and is used to heat the metal to a preset temperature;
[0023] a first roller and a second roller, wherein the first roller and the second roller are disposed in the vacuum chamber, and the first roller and the second roller are spaced apart from each other and are used to drive the polymer film to move;
[0024] A positioning roller, the positioning roller is arranged above the aluminum vapor evaporation device;
[0025] When manufacturing the composite current collector, one end of the polymer film is connected to the first roller, and the other end of the polymer film passes through the bottom of the positioning roller and is connected to the second roller.
[0026] Wherein, the aluminum vapor evaporation device is a distiller, and the positioning roller is arranged directly above the distiller.
[0027] A battery comprises a battery body, wherein the battery adopts the composite current collector manufactured by the composite current collector manufacturing method as the positive electrode current collector of the battery.
[0028] Further, the positive electrode of the battery includes NCM811, Super P, PVDF 5130 and CNT in a weight ratio of 96:1.8:1.7:0.5;
[0029] The negative electrode of the battery includes graphite, LA136D, Super P, CNT and CMC in a weight ratio of 96:2.3:0.9:0.4:0.4;
[0030] The electrolyte of the battery includes EMC and 1M LiPF6 or EC, and the volume ratio of EMC to 1M LiPF6 or EC is 7:3;
[0031] The separator of the battery includes a polyethylene film coated with ceramic.
[0032] By means of the above technical solution, the beneficial effects of the present invention are as follows:
[0033] 1. In the present application, it is only necessary to heat aluminum to a preset temperature in a vacuum environment, evaporate aluminum and deposit it on the surface of the polymer film to form a first aluminum layer, provide oxygen to react with aluminum, deposit an aluminum oxide layer on the surface of the first aluminum layer, and deposit the first aluminum layer and the aluminum oxide layer on both sides of the polymer film to obtain a composite current collector. This method has low production cost;
[0034] 2. The current collector disclosed in the present application is composed of staggered aluminum and chlorine trioxide layers. Nano-scale aluminum oxide reduces the ductility of the aluminum layer, making it more likely to crack on its own under deformation load. Therefore, at the moment when the battery cell structure is damaged and short-circuited, it can automatically break the circuit by cutting off the electronic channel, eliminating the risk of fire and explosion of the battery cell.
[0035] In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are specifically cited below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 is a schematic diagram of the structure of depositing a first aluminum layer in an embodiment of the present invention;
[0038] Figure 2 is a schematic diagram of the structure of depositing an aluminum oxide layer in an embodiment of the present invention;
[0039] Figure 3Schematic diagram of the structure of the current collector according to an embodiment of the present invention.
[0040] The figure markings of the above drawings are: 1. vacuum chamber; 2. distiller; 3. first roller; 4. second roller; 5. polymer film; 6. positioning roller; 7. polymer film roll; 8. aluminum ball; 9. first aluminum layer; 10. aluminum oxide layer. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] It should be noted that, in the description of the present invention, the terms "first", "second", etc. are only used for descriptive purposes and to distinguish similar objects. There is no order of precedence between the two, and they cannot be understood as indicating or implying relative importance. In addition, in the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0043] Combination Figure 1-3 As shown, the present application discloses a device for making a composite current collector, comprising:
[0044] Vacuum chamber 1;
[0045] An aluminum vapor evaporation device, which is disposed in the vacuum chamber 1 and is used to heat the metal to a preset temperature;
[0046] A first roller 3 and a second roller 4, wherein the first roller 3 and the second roller 4 are arranged in the vacuum chamber 1, and the first roller 3 and the second roller 4 are arranged at an interval and are used to drive the polymer film 5 to move;
[0047] A positioning roller 6, wherein the positioning roller 6 is arranged above the aluminum vapor evaporation device;
[0048] When manufacturing the composite current collector, one end of the polymer film 5 is connected to the first roller 3 , and the other end of the polymer film 5 passes through the bottom of the positioning roller 6 and is connected to the second roller 4 .
[0049] The aluminum vapor evaporation device is a distiller 2 , and the positioning roller 6 is arranged directly above the distiller 2 .
[0050] The steps of making a composite current collector using the above-mentioned device for making a composite current collector are as follows:
[0051] The polymer film roll 7 is placed on the first roller 3, and the polymer film 5 passes through the positioning roller 6 and is connected to the second roller 4;
[0052] Optionally, the polymer film roll 7 can be any one of PET, PP, and PI. In the present application, the polymer film roll 7 is a polyethylene terephthalate film.
[0053] Optionally, the thickness of the polymer film 5 may be between 5 μm and 7 μm.
[0054] An aluminum ball 8 is placed in the distiller 2, and the distiller 2 heats the aluminum ball 8 to 1100° C. to 1400° C., so that aluminum atoms of the aluminum ball 8 evaporate and are deposited on the surface of the polymer film 5. During the deposition process, the second roller 4 rotates to move the polymer film 5 from the first roller 3 toward the second roller 4 at a speed of 0.8 m / s to 1.2 m / s, thereby depositing a first aluminum layer 9 with a thickness of 0.8 μm to 1.2 μm on the surface of the polymer film 5;
[0055] When the polymer film roll 7 on the first roller 3 is completely wound on the second roller 4, oxygen is injected into the vacuum chamber, the distiller 2 is maintained at 1100° C. to 1400° C., the first roller 3 is rotated to move the polymer film 5 from the second roller 4 toward the first roller 3 at a speed of 3 m / s to 5 m / s, the aluminum balls 8 evaporate and react with oxygen to generate aluminum oxide, and an aluminum oxide layer 10 with a thickness of 0.9 nm to 1.1 nm is deposited on the surface of the first aluminum layer 9;
[0056] The first aluminum layer 9 and the aluminum oxide layer 10 are deposited on both sides of the polymer film 5 to obtain a composite current collector.
[0057] Through the above scheme, the aluminum ball 8 can be evaporated and deposited on the surface of the polymer film 5 to form a first aluminum layer 9 by simply heating the aluminum ball 8 to a preset temperature in a vacuum environment. By providing oxygen to react with aluminum, an aluminum oxide layer 10 can be deposited on the surface of the first aluminum layer 9. The first aluminum layer 9 and the aluminum oxide layer 10 are deposited on both sides of the polymer film 5 to obtain a composite current collector. This method has a low manufacturing cost, and the composite current collector can automatically break the circuit by cutting off the electronic channel at the moment when the battery cell structure is damaged and short-circuited, eliminating the risk of fire and explosion of the battery cell.
[0058] Embodiment 1:
[0059] A polyethylene terephthalate film roll with a thickness of 5 μm is placed on the first roller 3, and the polyethylene terephthalate film passes through the positioning roller 6 and is connected to the second roller 4;
[0060] An aluminum ball 8 is placed in the distiller 2, and the distiller 2 heats the aluminum ball 8 to 1400° C., so that aluminum atoms of the aluminum ball 8 evaporate and are deposited on the surface of the polyethylene terephthalate film. During the deposition process, the second roller 4 rotates to move the polyethylene terephthalate film from the first roller 3 toward the second roller 4 at a speed of 1 m / s, thereby depositing a first aluminum layer 9 with a thickness of 1 μm on the surface of the polyethylene terephthalate film;
[0061] When the polyethylene terephthalate film roll on the first roller 3 is completely wound on the second roller 4, oxygen is injected into the vacuum chamber, the distiller 2 is maintained at 1400° C., the first roller 3 is rotated to move the polyethylene terephthalate film from the second roller 4 toward the first roller 3 at a speed of 4 m / s, the aluminum balls 8 evaporate and react with oxygen to generate aluminum oxide, and a 1 nm thick aluminum oxide layer 10 is deposited on the surface of the first aluminum layer 9;
[0062] A first aluminum layer 9 with a thickness of 1 μm and an aluminum oxide layer 10 with a thickness of 1 nm are deposited on both sides of the polymer film 5 to obtain a first composite current collector.
[0063] Embodiment 2:
[0064] A polyethylene terephthalate film roll with a thickness of 6 μm is placed on the first roller 3, and the polyethylene terephthalate film passes through the positioning roller 6 and is connected to the second roller 4;
[0065] An aluminum ball 8 is placed in the distiller 2, and the distiller 2 heats the aluminum ball 8 to 1400° C., so that aluminum atoms of the aluminum ball 8 evaporate and are deposited on the surface of the polyethylene terephthalate film. During the deposition process, the second roller 4 rotates to move the polyethylene terephthalate film from the first roller 3 toward the second roller 4 at a speed of 1 m / s, thereby depositing a first aluminum layer 9 with a thickness of 1 μm on the surface of the polyethylene terephthalate film;
[0066] When the polyethylene terephthalate film roll on the first roller 3 is completely wound on the second roller 4, oxygen is injected into the vacuum chamber, the distiller 2 is maintained at 1400° C., the first roller 3 is rotated to move the polyethylene terephthalate film from the second roller 4 toward the first roller 3 at a speed of 6 m / s, the aluminum balls 8 evaporate and react with oxygen to generate aluminum oxide, and a 0.5 nm thick aluminum oxide layer 10 is deposited on the surface of the first aluminum layer 9;
[0067] A first aluminum layer 9 with a thickness of 1 μm and an aluminum oxide layer 10 with a thickness of 0.5 nm are deposited on both sides of the polymer film 5 to obtain a second composite current collector.
[0068] Comparative Example 1:
[0069] A polyethylene terephthalate film roll with a thickness of 7 μm is placed on the first roller 3, and the polyethylene terephthalate film passes through the positioning roller 6 and is connected to the second roller 4;
[0070] An aluminum ball 8 is placed in the distiller 2, and the distiller 2 heats the aluminum ball 8 to 1400° C., so that aluminum atoms of the aluminum ball 8 evaporate and are deposited on the surface of the polyethylene terephthalate film. During the deposition process, the second roller 4 rotates to move the polyethylene terephthalate film from the first roller 3 toward the second roller 4 at a speed of 0.25 m / s, thereby depositing a first aluminum layer 9 with a thickness of 10 μm on the surface of the polyethylene terephthalate film;
[0071] When the polyethylene terephthalate film roll on the first roller 3 is completely wound on the second roller 4, oxygen is injected into the vacuum chamber, the distiller 2 is maintained at 1400° C., the first roller 3 is rotated to move the polyethylene terephthalate film from the second roller 4 toward the first roller 3 at a speed of 6 m / s, the aluminum balls 8 evaporate and react with oxygen to generate aluminum oxide, and a 0.5 nm thick aluminum oxide layer 10 is deposited on the surface of the first aluminum layer 9;
[0072] A 10 μm thick first aluminum layer 9 and a 0.5 nm thick aluminum oxide layer 10 are deposited on both sides of the polymer film 5 to obtain a third composite current collector.
[0073] The thermal properties of the composite current collector prepared by the composite current collector preparation method disclosed in this application were verified by thermogravimetric testing:
[0074] The initial mass of 6 mg of various samples was pressed into a ceramic crucible and heated from 50°C to 1000°C at a heating rate of 10°C / min in a high-purity flowing argon environment. The remaining sample mass was measured and the test results are as follows:
[0075] sample Embodiment 1 Embodiment 2 Comparative Example 3 Pure aluminum foil Carbon coated aluminum foil Initial Quality 6mg 6mg 6mg 6mg 6mg Final Quality 5.51mg 5.76mg 5.26mg 5.2mg 5.06mg
[0076] It can be understood that the better the heat resistance of the sample is, the less mass it loses as the temperature increases.
[0077] It can be seen from the test results that the heat resistance of the current collector disclosed in this application is better than that of common aluminum foil, carbon-coated aluminum foil, etc. on the market.
[0078] The ductility of the composite current collector prepared by the composite current collector preparation method disclosed in this application was verified by a tensile test:
[0079] The sample was fixed on the positioner by four stainless steel columns;
[0080] Clamp one end of the sample with the mobile fixture, and drive the mobile fixture to move along the Y axis at a speed of 1.0 μm / s by the driving motor until the sample is broken;
[0081] The mechanical deformation of the sample was recorded using a high-resolution CCD camera;
[0082] An alignment camera is used to monitor the horizontal position of the sample and calculate the elongation at sample break:
[0083] Example Embodiment 1 Embodiment 2 Comparative Example 3 Pure aluminum foil Carbon coated aluminum foil Elongation 3.80% 3.90% 2.50% 3.30% 3.45%
[0084] Among them, it can be understood that the higher the ductility of the sample before it breaks, the better the ductility of the sample.
[0085] Experimental results show that the ductility of the current collector disclosed in this application is better than that of common aluminum foil, carbon-coated aluminum foil, etc. on the market.
[0086] The present application also discloses a battery, comprising a battery body, wherein the positive electrode of the battery comprises NCM811, Super P, PVDF 5130 and CNT, and the weight ratio thereof is 96:1.8:1.7:0.5;
[0087] The negative electrode of the battery includes graphite, LA136D, Super P, CNT and CMC in a weight ratio of 96:2.3:0.9:0.4:0.4;
[0088] The electrolyte of the battery includes EMC and 1M LiPF6 or EC, and the volume ratio of EMC to 1M LiPF6 or EC is 7:3;
[0089] The separator of the battery adopts a polyethylene film coated with ceramic;
[0090] The battery uses 6 μm thick copper foil as the negative electrode current collector.
[0091] Embodiment 4:
[0092] The battery above uses the first composite current collector in Example 1 as the positive electrode current collector.
[0093] Embodiment five:
[0094] The above battery uses the second composite current collector in Example 2 as the positive electrode current collector.
[0095] Embodiment six:
[0096] The above battery uses the third composite current collector in Example 3 as the positive electrode current collector.
[0097] Embodiment seven:
[0098] The above battery uses pure aluminum foil as the positive electrode current collector.
[0099] Embodiment eight:
[0100] The above battery uses carbon-coated aluminum foil as the positive electrode current collector.
[0101] The following experiments are conducted to verify that the composite current collector prepared by the composite current collector preparation method disclosed in the present application can automatically break the circuit by cutting off the electronic channel at the moment when the battery cell structure is damaged and short-circuited, thereby eliminating the risk of fire and explosion of the battery cell:
[0102] A stainless steel nail with a diameter of 3 mm was used to pass through the center of the battery at a speed of 10 mm / s. The experimental results are as follows:
[0103]
[0104] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a composite current collector, characterized in that: include; A first roller and a second roller are arranged in a vacuum chamber, wherein the first roller unwinds the polymer film and the second roller rewinds the polymer film; Using an aluminum vapor evaporation device, vapor aluminum is evaporated and deposited onto the surface of the unfolded portion of the polymer film. During the deposition process, the polymer film moves from the first roller toward the second roller at a speed of 0.8 m / s to 1.2 m / s, thereby depositing a first aluminum layer with a thickness of 0.8 μm to 1.2 μm on the surface of the polymer film; Injecting oxygen into the vacuum chamber, under the action of the aluminum vapor evaporation device, the vapor aluminum and oxygen react to generate aluminum oxide and deposit it on the surface of the first aluminum layer. During the deposition process, the polymer film having the first aluminum layer moves from the second roller toward the first roller at a speed of 3m / s to 5m / s, thereby depositing an aluminum oxide layer with a thickness of 0.9nm to 1.1nm on the surface of the first aluminum layer; The first aluminum layer and the aluminum oxide layer are deposited on both side surfaces of the polymer film to obtain a composite current collector.
2. The method for preparing a composite current collector according to claim 1, wherein: During the deposition process, the aluminum vapor evaporation device is heated to 1100°C to 1400°C.
3. The method for preparing a composite current collector according to claim 2, wherein: During the deposition of the first aluminum layer, the polymer film moves from the first roller toward the second roller at a speed of 1 m / s, and a first aluminum layer with a thickness of 1 μm is deposited on the surface of the polymer film.
4. The method for preparing a composite current collector according to claim 3, wherein: During the deposition of the aluminum oxide layer, the polymer film moves from the second roller toward the first roller at a speed of 4 m / s, and a 1 nm thick aluminum oxide layer is deposited on the surface of the first aluminum layer.
5. The method for preparing a composite current collector according to claim 3, wherein: During the deposition of the aluminum oxide layer, the polymer film moves from the second roller toward the first roller at a speed of 6 m / s, and a 0.5 nm thick aluminum oxide layer is deposited on the surface of the first aluminum layer.
6. The method for preparing a composite current collector according to claim 1, wherein: The polymer film includes any one of PET, PP and PI, and the polymer film has a thickness of 5 μm to 7 μm.
7. A composite current collector prepared by the method according to any one of claims 1 to 6, characterized in that: include: A polymer film layer, wherein the polymer film layer is made of polyethylene terephthalate; A first aluminum layer, wherein the first aluminum layer is disposed on both side surfaces of the polymer film layer; An aluminum oxide layer is disposed on a side of the first aluminum layer away from the polymer film layer.
8. A device for making a composite current collector according to any one of claims 1 to 6, characterized in that: include: Vacuum chamber; An aluminum vapor evaporation device, which is disposed in the vacuum chamber and is used to heat the metal to a preset temperature; a first roller and a second roller, wherein the first roller and the second roller are disposed in the vacuum chamber, and the first roller and the second roller are spaced apart from each other and are used to drive the polymer film to move; A positioning roller, the positioning roller is arranged above the aluminum vapor evaporation device; When manufacturing the composite current collector, one end of the polymer film is connected to the first roller, and the other end of the polymer film passes through the bottom of the positioning roller and is connected to the second roller.
9. A battery, comprising a battery body, characterized in that: The battery adopts the composite current collector according to claim 7 as the positive electrode current collector of the battery.
10. The method for preparing a composite current collector according to claim 9, wherein: The positive electrode of the battery includes NCM811, Super P, PVDF 5130 and CNT, and the weight ratio is 96: 1.8:1.7:0.5; The negative electrode of the battery includes graphite, LA136D, Super P, CNT and CMC in a weight ratio of 96:2.3:0.9:0.4:0.4; The electrolyte of the battery includes EMC and 1M LiPF6 or EC, and the volume ratio of EMC to 1M LiPF6 or EC is 7:3; The separator of the battery includes a polyethylene film coated with ceramic.